(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
In the present study, we evaluated the inhibitory effect of trichostatin A on the asexual growth of bovine, equine, and canine Babesia parasites in vitro as well as on the in vivo growth of Babesia microti (B.microti) in mice. The growth of Babesia bovis (B.bovis), Babesia bigemina (B.bigemina), Babesia caballi (B.caballi), Theileria equi (T.equi), and Babesia gibsoni (B.gibsoni) species was significantly inhibited (P < 0.05) by very low concentrations of trichostatin A (IC50 values = 2.6, 2.4, 2.3, 2.4, and 2.3 nM, respectively). Furthermore, in B.microti-infected mice, trichostatin A caused significant higher (P < 0.05) inhibition of the growth of B.microti at the dose of 2 mg/kg body weight than that in the control group. These results indicated the trichostatin A might be a chemotherapeutic agent for treatment of babesiosis. DOI: http://dx.doi.org/10.5564/mjas.v11i2.210 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.24-26